Agnostic stacking of intergalactic doublet absorption: measuring the Ne viii population. Issue 1 (5th February 2018) - Frank, Stephan; Pieri, Matthew M; Mathur, Smita; Danforth, Charles W; Shull, J Michael
Abstract: We present a blind search for doublet intergalactic metal absorption with a method dubbed 'agnostic stacking'. Using a forward-modelling framework, we combine this with direct detections in the literature to measure the overall metal population. We apply this novel approach to the search for Ne viii absorption in a set of 26 high-quality COS spectra. We probe to an unprecedented low limit of log N >12.3 at 0.47≤ z ≤1.34 over a path-length Δ z = 7.36. This method selects apparent absorption without requiring knowledge of its source. Stacking this mixed population dilutes doublet features in composite spectra in a deterministic manner, allowing us to measure the proportion corresponding to Ne viii absorption. We stack potential Ne viii absorption in two regimes: absorption too weak to be significant in direct line studies (12.3 < log N < 13.7), and strong absorbers (log N > 13.7). We do not detect Ne viii absorption in either regime. Combining our measurements with direct detections, we find that the Ne viii population is reproduced with a power-law column density distribution function with slope $β = -1.86 ^{+0.18 }_{ -0.26}$ and normalization log $f_{13.7} = -13.99 ^{+0.20 }_{ -0.23}$, leading to an incidence rate of strong Ne viii absorbers ${\rm d}n/{\rm d}z =1.38 ^{+0.97 }_{ -0.82}$ . We infer a cosmic mass density for Ne viii gas with 12.3 < log N < 15.0 of $Ω _{{{\rm Ne \, \small {VIII}}}} = 2.2 ^{+1.6 }_{ _-1.2} × 10^{-8}$, a value significantly lower that than predicted by recent simulations. We translate this density into an estimate of the baryon density Ω b ≈ 1.8 × 10 −3, constituting 4 per cent of the total baryonic mass.